(untitled) (Baghdad Science Journal, 2024)
In this study, mesoporous silica (MPS) is made using the sol-gel method from a cheap source (Na2SiO3) using the surfactant hydroxycetyl hydroxyethyl dimonium chloride as a template. The task is the adsorption-based removal of the medication metoprolol (MP) at concentrations between 10 and 50 ppm. Variables such as: contact time, dose of adsorbent, starting concentration of adsorbate, and adsorption temperature were studied which show the equilibrium time and adsorbent dose are 40 min and 0.05 g respectively. The Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich isotherm models were fitted to the data obtained from the experiments. Comparing the outcomes showed that, of the four investigated isotherm models, the Freundlich equation model could accurately predict these data. Based on adsorption isotherm analysis, as the temperature was raised, it was discovered that the amount of adsorption rose and that the adsorption was advantageous and may be a physical process. In addition, the study involved estimation of ∆H°, ∆S°, and ∆G° as thermodynamic parameters. ∆G° values were discovered to be between -20.24 and -26.22 kJ/mol and reduced when temperature rose, indicating that adsorption may be become more spontaneous at higher temperatures. The value of ∆H° was 38.10 kJ/mol indicate adsorption process was physical in character. ∆S° for this process had a value of 199.14 J/mol K which suggested the increased degree of flexibility of the adsorbed MP. The sign of ∆G° and ∆H° were suggested spontaneous and endothermic of the process